Rapid molecular screening for multidrug‐resistant tuberculosis in a resource‐limited region of China. Issue 10 (17th July 2014) - Zhang, Dan; Liu, Beizhong; Wang, Yufeng; Pang, Yu
Abstract Objective To investigate the molecular characteristics of MDR and XDR strains circulating in Chongqing, China. Methods The drug target genes conferring for rifampicin (RIF), isoniazid (INH), ethambutol (EMB), ofloxacin (OFLX) and kanamycin (KAN) resistance were screened by DNA sequencing to determine the mutation frequencies in this area. Results Drug susceptibility of 208 MDR isolates revealed that 132 (63.46%) were resistant to streptomycin (SM), 96 (46.15%) to ethambutol (EMB), 51 (24.52%) to ofloxacin (OFLX), and 26 (12.50%) to kanamycin (KAN); six (2.88%) isolates had XDR profiles. In comparison with the drug susceptibility phenotype, the sensitivity of drug resistance by DNA sequencing was 91.83% for RIF, 87.50% for INH, 66.67% for EMB, 74.51% for OFLX and 53.85% for KAN resistance. 12.50% of EMB‐ and 1.27% of OFLX‐susceptible isolates were harboured genetic mutations in embB and gyrA, respectively. Conclusion Our findings demonstrate that the hot‐spot regions localised in rpoB, katG and inhA genes serve as excellent markers for the corresponding drug resistance, while EMB, OFLX or KAN drug‐resistant TB cases may not be identifiable by scanning embB, gyrA, rrs and eis promoter in Chongqing, indicating that further studies on the drug resistance mechanisms of EMB, OFLX and KAN are urgently needed to elucidate the low sensitivity between genomic substitutions and drug‐resistant phenotype.